Insights into the localization and function of myomaker during myoblast fusion - Gamage, Dilani G. (J Biol Chem, 2017)
Multinucleated skeletal muscle fibers form through the fusion of myoblasts during development and regeneration. Previous studies identified myomaker (Tmem8c) as a muscle-specific membrane protein essential for fusion. However, the specific function of myomaker and how its function is regulated are unknown. To explore these questions, we first examined the cellular localization of endogenous myomaker. Two independent antibodies showed that whereas myomaker does localize to the plasma membrane in cultured myoblasts, the protein also resides in the Golgi and post-Golgi vesicles. These results raised questions regarding the precise cellular location of myomaker function and mechanisms that govern myomaker trafficking between these cellular compartments. Using a synchronized fusion assay, we demonstrated that myomaker functions at the plasma membrane to drive fusion. Trafficking of myomaker is regulated by palmitoylation of C-terminal cysteine residues that allows Golgi localization. Moreover, dissection of the C terminus revealed that palmitoylation was not sufficient for complete fusogenic activity suggesting a function for other amino acids within this C-terminal region. Indeed, C-terminal mutagenesis analysis highlighted the importance of a C-terminal leucine for function. These data reveal that myoblast fusion requires myomaker activity at the plasma membrane and is potentially regulated by proper myomaker trafficking.